Synthesis and Post‐Polymerization Modification of Poly(N‐(4‐Vinylphenyl)Sulfonamide)s. Issue 10 (24th May 2021) - Molle, Edgar; Mutlu, Hatice; Theato, Patrick
Abstract : Frontispiece : In article number 2100063 by Patrick Theato, Hatice Mutlu, and Edgar Molle, a set of novel poly(N‐(4‐vinylphenyl)sulfonamide) s featuring varying electron densities is prepared in a straightforward fashion and subsequently used in post‐polymerization modification reactions via aza‐Michael addition with different electron‐defi cient alkenes as Michael acceptors for the facile synthesis of polymeric protected ‐amino acid derivatives.